Tujuan Pemidanaan dalam Penjatuhan Pidana Tambahan Pembayaran Uang Pengganti Tindak Pidana Korupsi - Rachmadi, Moch Rizky; Dollu, Daud Yaferson (Penerbit Goodwood, 2024)
Purpose: This study examines the rationale behind judges’ decisions to impose additional criminal penalties in the form of restitution payments in corruption cases, focusing on the extent to which such penalties align with the objectives of sentencing and restorative justice. Research methodology: This study employs a normative juridical approach supported by case, statute, and conceptual analyses. Data were collected from relevant court rulings and analyzed descriptively and qualitatively using legal interpretations. Results: The findings show that while judges tend to apply retributive justice by imposing prison sentences, the enforcement of restitution payments remains inconsistent. Some defendants return all or part of the state losses, while others do not comply. Conclusions: The imposition of restitution penalties formally supports the objective of recovering state loss. However, the actual implementation reveals gaps that hinder the full realization of restorative justice. Limitations: The study is limited by incomplete data accessibility and the geographical scope of the case studies, which may not comprehensively represent national practice. Contribution: This study highlights the need to reformulate corruption sentencing laws to prioritize restitution and offers a restorative justice model to balance punishment with asset recovery.